2014
DOI: 10.1159/000360285
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effectiveness and Safety of Nabiximols (Tetrahydrocannabinol/Cannabidiol Oromucosal Spray) in Clinical Practice

Abstract: Background: Nabiximols (Sativex®), in a cannabinoid-based oromucosal spray, is an add-on therapy option for patients with moderate to severe multiple sclerosis spasticity (MSS) resistant to other medications. The study objective was to provide long-term data on clinical outcomes, tolerability, quality of life and treatment satisfaction for MSS patients receiving nabiximols in routine care. Methods: This was the 12-month prolongation of the MOVE 2 study, an observational, prospective, multi-centre 3-month non-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 18 publications
3
44
0
1
Order By: Relevance
“…None of the 3 deaths that occurred was considered by the treating physician to be related to THC:CBD spray. The tolerability profile of THC:CBD spray in Spanish patients aligns with that reported in the observational MObility improVEment 2 (MOVE 2) study from Germany in which THC:CBD spray was prescribed to patients with treatment-resistant MS spasticity (n=300) according to approved labelling [19,20].…”
Section: Polyuriasupporting
confidence: 69%
“…None of the 3 deaths that occurred was considered by the treating physician to be related to THC:CBD spray. The tolerability profile of THC:CBD spray in Spanish patients aligns with that reported in the observational MObility improVEment 2 (MOVE 2) study from Germany in which THC:CBD spray was prescribed to patients with treatment-resistant MS spasticity (n=300) according to approved labelling [19,20].…”
Section: Polyuriasupporting
confidence: 69%
“…This latter aspect remains the major challenge for the future and it may be facilitated by the recent approval of the first cannabinoidbased medicines [e.g., Sativex (GWPharma), Epidiolex (GWPharma)] available for clinical use. These formulations, and additional combination of phytocannabinoids, present 2 important advantages: 2) its safety demonstrated in previous studies [169], despite the fact that manipulation of the endocannabinoid system may be harmful in certain circumstances [1], a fact deserving additional investigation; and 2) its broad-range profile that appears to be adequate for diseases in which different cytotoxic mechanisms cooperate to damage specific neuronal subpopulations. Therefore, it is expected and desirable that the issue recruits an important amount of clinical research in the future, which will allow for the promising expectation generated around the progress of these molecules from the present preclinical evidence to a real clinical exploitation.…”
Section: Concluding Remarks and Future Perspectivesmentioning
confidence: 99%
“…25 Given that this improvement occurred without a corresponding significant change in mood, the authors suggest that patients have felt a benefit from intrinsic reduction in pain, sleep improvement, or both. 25 A recent review, including four randomized controlled trials, 21,29,42,43 two extension studies, 27,44 and a prospective noninterventional study in clinical practice with a long-term extension phase, 45,46 has shown that approximately 40% of patients with moderate-tosevere spasticity resistant to the current available oral antispasticity agents reached relevant symptomatic relief with Sativex oromucosal spray that was accompanied by improvement of spasticity-associated symptoms or functional impairment, including sleep quality. 41 In particular, in one study, 44 the proportion of patients who rated their sleep quality as "bad" or "very bad" decreased from 13% to 11%, whereas those who rated it as "good" or "very good" increased from 50% to 59%; in another investigation, 21 61% of Sativex responders also achieved a ⩾30% improvement on the sleep quality Numerical Rating Scale (NRS); in the prospective observational MOVE 2 study, 45 the addon therapy with Sativex produced a significant 24.3% decrease from baseline to week 4 in the mean sleep disturbances NRS score, and among patients who progressed to the 12-month extension study, 46 there was a highly significant 37.2% reduction from baseline in the mean sleep disruption NRS score.…”
Section: Cannabis-based Extractsmentioning
confidence: 99%